One-beam dynamic ion mixing applied to coat elements onto sophistically shaped objects - Boyko, E.B.; Komarov, F.F.; Jukowski, P.; Karwat, C.; Kolasik, M.; Kozak, C. (Физическая инженерия поверхности, 2007)
Recently suggested single-ion-beam setup for ion-beam assisted deposition (IBAD) of layers with
various composition including the sputter target in a form of hollow truncated cone made of the
material to be deposited allows the use of a single ion beam (e.g., noble gas) for simultaneous layer
deposition and ion-beam mixing. Such a setup can also be applied for coating deposition on the
surfaces having sophisticated geometric shape. In the present work single-beam IBAD was used for
deposition of Ni and Mo coatings onto the surface of ball fingers. The Rutherford backscattering was
used for evaluating the coating thickness distributions along the spherical surface of the aluminium
ball fingers. It is shown that the results can be explained in terms of space distribution of the sputtered
atoms inside the conical target. Запропоновано систему з одним іонним пучком
для іонно-асистуємого нанесення (ІАН) шарів
різної композиції, яка включає мішень, що розпорошується, у формі усіченого порожнього конуса, виготовленого з матеріалу, що буде наноситися. У цій системі одночасно реалізується як
нанесення шару, так і іонно-променеве перемішування його з підкладинкою. Така система
може використовуватися і для нанесення покриттів на вироби довільної геометричної форми. У
цій роботі однопучкове ІАН застосовувалося для
осадження шарів Ni і Mo на поверхню алюмінієвих кульових пальців. За допомогою зворотного резерфордівського розсіювання іонів He+
визначався розподіл товщини покриття уздовж
сферичної поверхні кульових пальців. Показано,
що отримані результати можна пояснити на основі даних по просторовому розподілі рос-пилених атомів усередині полою конічної мішені. Предложена система с одним ионным пучком для
ионно-ассистируемого нанесения (ИАН) слоев
различной композиции, которая включает распыляемую мишень в форме усеченного полого
конуса, изготовленного из материала, который будет наноситься. В этой системе одновременно реализуется как нанесение слоя, так и ионно-луче-
вое перемешивание его с подложкой. Такая система может использоваться и для нанесения покрытий на изделия произвольной геометрической
формы. В настоящей работе однопучковое ИАН
применялось для осаждения слоев Ni и Mo на
поверхность алюминиевых шаровых пальцев. С
помощью обратного резерфордовского рассеяния
ионов He+ определялось распределение толщины
покрытия вдоль сферической поверхности шаровых пальцев. Показано, что полученные результаты можно объяснить с точки зрения пространственного распределения распыленных атомов внутри полой конической мишени.